2013
DOI: 10.1099/mic.0.068957-0
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Aquincola tertiaricarbonis L108 on the fuel oxygenate intermediate tert-butyl alcohol induces aerobic anoxygenic photosynthesis at extremely low feeding rates

Abstract: Aerobic anoxygenic photosynthesis (AAP) is found in an increasing number of proteobacterial strains thriving in ecosystems ranging from extremely oligotrophic to eutrophic. Here, we have investigated whether the fuel oxygenate-degrading betaproteobacterium Aquincola tertiaricarbonis L108 can use AAP to compensate kinetic limitations at low heterotrophic substrate fluxes. In a fermenter experiment with complete biomass retention and also during chemostat cultivation, strain L108 was challenged with extremely lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…S2A) (10). The draft genome sequencing assembly and annotation revealed that the RN12 strain harbored the previously characterized gene clusters for biosynthesis of bacteriochlorophyll (bch) and anoxygenic photosynthesis, as well as the gene for leucine/isovalerate utilization (liu), encoded in the A. tertiaricarbonis strain L108 (3,11). The average nucleotide identity (ANI) of the common genes between L108 and RN12 was also relatively high.…”
Section: Resultsmentioning
confidence: 95%
“…S2A) (10). The draft genome sequencing assembly and annotation revealed that the RN12 strain harbored the previously characterized gene clusters for biosynthesis of bacteriochlorophyll (bch) and anoxygenic photosynthesis, as well as the gene for leucine/isovalerate utilization (liu), encoded in the A. tertiaricarbonis strain L108 (3,11). The average nucleotide identity (ANI) of the common genes between L108 and RN12 was also relatively high.…”
Section: Resultsmentioning
confidence: 95%
“…Bacteriochlorophyll synthesis has been shown to be induced under carbon limitation (Sato-Takabe et al, 2014) or under osmotic stress (Biebl, 2006), and light prolonged survival of the Roseobacter species Dinoroseobacter shibae under starvation (Soora and Cypionka, 2013;Soora et al, 2015). During biodegradation of tertyl-butyl alcohols in a chemostat, bacteriochlorophyll synthesis was unexpectedly induced at extremely low substrate concentrations; the photosynthesis gene cluster was subsequently detected in the genome of the strain (Rohwerder et al, 2013). The first metabolic model of an AAP taking into account the role of light as an additional source of energy demonstrated a direct effect of light on swimming speed of D. shibae (Rex et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2 ). Only two species, Roseateles depolymerans ( 42 ) and Aquincola tertiaricarbonis ( 27 , 35 ) have been described as AAP bacteria in Betaproteobacteria . Other aerobic Betaproteobacteria such as Methyloversatilis unversalis and Limnohabitans sp.…”
Section: Discussionmentioning
confidence: 99%
“…Elioraea tepidiphila , which has been described as a non-phototrophic bacterium, was shown to have pufLM gene sequences in its genome ( 1 ). A. tertiaricarbonis was also initially described as a non-phototrophic bacterium that does not produce BChl, but was subsequently found to produce BChl under different culture conditions ( 27 , 35 ). These examples suggest that some bacteria described as non-phototrophic may have photosynthesis genes and produce a photosynthetic apparatus under some conditions.…”
Section: Discussionmentioning
confidence: 99%